1991
DOI: 10.2307/3586979
|View full text |Cite
|
Sign up to set email alerts
|

Listening in the Native and Second/Foreign Language: Toward an Integration of Research and Practice

Abstract: After reviewing research on native language (NL) listening, the article discusses (a) the importance of listening in second language acquisition, (b) factors that influence success or failure of comprehension of first or second language messages, (c) the role of listening in the L2 curriculum, (d) posited models of NL and L2 listening comprehension, and (e) proposed taxonomies of listening skills and pedagogical activities. The essay argues that researchers and practitioners working together can foster greater… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
81
0
8

Year Published

1997
1997
2016
2016

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 158 publications
(90 citation statements)
references
References 63 publications
1
81
0
8
Order By: Relevance
“…and other external environmental factors such as noise and inaudibility can create anxiety among L2 learners. However Dunkel (1991) believes that those students who do not have the confidence might experience anxiety more. In a study done by Vogely (1998), students reported the cause of their anxiety on being more concentrated on the nature of speed, level of difficulty, ambiguity, lack of visual support and lack of repetition.…”
Section: Foreign Language Listening Anxietymentioning
confidence: 99%
See 1 more Smart Citation
“…and other external environmental factors such as noise and inaudibility can create anxiety among L2 learners. However Dunkel (1991) believes that those students who do not have the confidence might experience anxiety more. In a study done by Vogely (1998), students reported the cause of their anxiety on being more concentrated on the nature of speed, level of difficulty, ambiguity, lack of visual support and lack of repetition.…”
Section: Foreign Language Listening Anxietymentioning
confidence: 99%
“…In fact, many students who are now expressing discontent and have conveyed either implicitly or explicitly are suffering from known as anxiety and identify themselves as anxious language learners. According to Worde (1998), the concept of anxiety is concentrated frequently throughout language learning literature; these studies (Aida, 1994;Bailey, 1983;Crookal and Oxford, 1991;Horwitz, Horwitz, & Cope, 1986;Horwitz & Young, 1991;MacIntyre, 1995;MacIntyre & Gardner, 1988, 1989, 1991Young, l992) have examined different perspectives of anxiety, and have consecutively generated varying definitions. These studies have also concentrated on different language outcomes, like the rate of second language acquisition, performance of learners in language classrooms, and performance in language testing.…”
Section: Introductionmentioning
confidence: 99%
“…So, the study of techniques to enhance listening comprehension is nowadays considered as a building block in second language acquisition researches (Dunkel, 1991). It is also believed that when teachers provide students with abundant opportunities for listening practice, the process of developing useful listening strategies will be best achieved.…”
Section: Introductionmentioning
confidence: 99%
“…It is the only foreign language skill in which a participant has no control over the process. Writing and reading are important for basic language abilities, but the capability of listening to a foreign language is important in language learning (Anderson and Lynch, 1988;Dunkel, 1991;Rubin, 1994) for fluency, speaking skills and the ability to communicate (Croom Helm Cross, 1998). Listening is a vital skill to acquire pronunciation, vocabulary, word stress, and syntax.…”
Section: Literature Reviewmentioning
confidence: 99%